The Effect of Political Alliances on Bilateral Trade Flows: The Case of North Korea. - Kim, Yujin. (Tufts University. Tisch Library., 2020)
The study explores whether alliance relationships influence bilateral trade flows in North Korea. Addressing endogeneity is pivotal in this study, as the opportunities to secure large trade volumes can motivate countries to form alliances. To tackle this issue, I note that although North and South Korea once constituted a single country and share similar cultural and geographical characteristics, they have demonstrated different alliance relationships. In other words, the communist government of North Korea has been allied with China, while South Korea, which is based on the free-market system, has long been allied with the US. Indeed, the data reveal that the US is South Korea's second-largest trade partner, whereas it is only the 19th for North Korea. To identify the role of political influence in their trade dynamics differences, I used an identification strategy that uses the division of Korea as an exogenous source of variation. The results show that North Korea tends to trade with its allied countries six times more than its non-allies, and the impact is larger for North Korea than South Korea.; 15-minute talk presented at the Tufts Graduate Student Council's 24th Graduate Student Research Symposium, March 6, 2020.